Fundamentals of Advanced Pyrometallurgy - Zhao, Baojun; Zhang, Jianliang; Ma, Xiaodong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Pyrometallurgy is considered to be an environmentally friendly technology in processing of primary and secondary raw materials. The continuous development of pyrometallurgical processes to treat more complex raw materials requires direct support from fundamental research. In this reprint, 18 papers focusing on recent investigations into the existing and new pyrometallurgical processes such as recovery of cobalt through chlorination-volatilization, the extraction of tungsten from low-grade concentrates, copper and lead smelting, ironmaking, and steelmaking are collected. This reprint is expected to serve as a valuable reference for academia and the industry working on thermodynamics, kinetics, and technological optimization and development.